2007
DOI: 10.2174/092986707781696609
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual Allergen Immunotherapy: Immunological Mechanisms and Prospects for Refined Vaccine Preparations

Abstract: Allergic diseases constitute a major health issue worldwide. Mainstay treatment constitutes allergen avoidance and pharmacotherapy for symptom relief, but allergen immunotherapy offers advantages of specific treatment with long lasting efficacy, and being able to modify the course of the disease. Conventional immunotherapy involves the subcutaneous injection of gradually increasing amounts of allergen extract but the use of current whole allergen extracts is restricted by the risk of adverse IgE-mediated event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 117 publications
(207 reference statements)
1
17
0
Order By: Relevance
“…Specific immunotherapy is also accompanied by decreased specific IgE, increased protective specific IgG 4 antibody levels, and reduced number and activation of mast cells, eosinophils, and basophils. [17][18][19][20][21][22] Stimulation of appropriate T-cell responses during allergen-specific immunotherapy is necessary for effective desensitization. 22 Conventional immunotherapy administers whole allergen extracts, but peptides containing T-cell epitopes of major allergens provide an effective, safer (non-IgE-reactive) alternative.…”
mentioning
confidence: 99%
“…Specific immunotherapy is also accompanied by decreased specific IgE, increased protective specific IgG 4 antibody levels, and reduced number and activation of mast cells, eosinophils, and basophils. [17][18][19][20][21][22] Stimulation of appropriate T-cell responses during allergen-specific immunotherapy is necessary for effective desensitization. 22 Conventional immunotherapy administers whole allergen extracts, but peptides containing T-cell epitopes of major allergens provide an effective, safer (non-IgE-reactive) alternative.…”
mentioning
confidence: 99%
“…The idea behind SLIT is that the allergen is captured within the oral mucosa by Langerhanslike dendritic cells expressing high-affinity IgE receptors, producing IL-10 and TGF-β [38]. The oral mucosa has a restricted number of proinflammatory cells, such as mast cells, and that contributes to the safety of SLIT [39]. Thus for our study we decided to investigate the effects on IL-10 and TGF-β as they are T regulatory dependent cytokines shown to be important in successful SLIT [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…131 The clinical trial results for tracheal administration have suggested that clinical efficacy is unproven and that the risk/benefit ratio is unfavorable. 132,133 SLIT The mechanisms behind SLIT include the production of blocking IgG4 antibodies, 134,135 the presence of high numbers of tolerogenic DC subsets, the induction of regulatory T cells, 136,137 and the programming of the immune system toward a regulatory state of unresponsiveness to specific allergens. SLIT may also increase IL-10, which has a clear role in suppressing allergic immune responses.…”
Section: Oralmentioning
confidence: 99%